Fixed, vertical road traffic signs Part 1. Fixed signs (BSI, 2007)
Road signs, Fixed, Signs, Vertical, Street furniture, Performance, Grades (quality), Retroreflective materials, Luminance, Reflection factor, Colorimetry, Colour, Loading, Lighting (road signs), Conformity, Performance testing